PENGGUNAAN BAHASA DALAM PELAYANAN PERIZINAN SANTRI DI KANTOR KEAMANAN PONDOK PESANTREN PUTRI UTARA DARUSSALAM BLOKAGUNG BANYUWANGI :KAJIAN SOSIOLINGUISTIK - Isti Nafiatus Sholichah (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research was conducted with the aim of describing the use of language performed by the waiter and the customer during the permit service along with the factors that influence it. This research uses Dell Hymes theory, namely SPEAKING. The method used is a qualitative method with the aim of describing the use of servant language and the factors that affect the diversity of languages in the security office. The method of data collection in this study uses the technique of listening to the language of the service free. The method of listening is done by taking notes while the conversation is taking place. The data that has been obtained are described and then sorted according to the data found. There are at least three languages used by the maids in the student permit service (Javanese, Osing, and Indonesian). The factors of language use that influence the language used by servants in security and order offices are age, mutual respect, and familiarity. The result of this research is that there are three languages used in the licensing service for students. The languages used are Javanese, Osing, and mixed languages.